Penggunaan Alat Bukti Surat Sebagai Upaya Penuntut Umum dalam Pembuktian Tindak Pidana Membujuk Anak Untuk Melakukan Perbuatan Cabul - Ignatius Ninorey (Verstek, 2019)
The purpose of this study is to discuss about, frstly whether the submission of proof of letter or Visum Et Repertum in a criminal act to persuade the child to commit lewd acts are in accordance with the provisions of the Criminal Procedure Code, secondly whether the evidence proof of letter or Visum Et Repertum in the criminal investigation to persuade the child to Performing lewd acts considered by a judge.      The results of this study indicate that the use of letter proof or Visum Et Repertum in a criminal act to persuade a child to commit obscene acts have complied with the provisions of Article 187 letter c of the Criminal Procedure Code, So that the explanation about the evidence of expert information must be based on the expertise and also there is an offcial statement in which in this case the expert information is completed and based on the Visum et Repertum considered by the judge as the basis for the cut off plus the testimony of the witness, the statement of the defendant and the evidence.Keywords: Letter or Visum Et Repertum, Evidence and Criminal pervert.